Let
, where A and C are square matrix. Show that det(M)=det(A)det(C)
I have the following idea but i dont have a concrete proof. We can perform elementary row operations on the matrix M. Eventually A and C will be a upper triangular matrix. Hence det(A) and det(C) will just be the product of their diagonal entries. On the other hand, M will also become an upper triangular matrix after the elementary row operations. Therefore, det(M)=product of its diagonal entries=product of diagonal entries of A * product of diagonal entries of C=det(A)det(C).